Caminando por los limina de la conjetura. A propósito del Heracles de Eurípides - Calderón Dorda, Esteban (AL. Rivista di studi di Anthologia Latina, 2022)
Abstract The present work consists of several notes on the text of Euripides’ Heracles (38-39, 62, 87, 126-128, 301, 319-320, 348-351, 364-367, 434-435, 483-484, 503, 508, 637-641, 831-832, 943-946, 1017). It is a defense of lectio tradita against emendatio ope ingenii.